Co-amorphous formulations of furosemide with arginine and p-glycoprotein inhibitor drugs - Ruponen, Marika (2021)
In this study, the amino acid arginine (ARG) and P-glycoprotein (P-gp) inhibitors verapamil hydrochloride (VER), piperine (PIP) and quercetin (QRT) were used as co-formers for co-amorphous mixtures of a Biopharmaceutics classification system (BCS) class IV drug, furosemide (FUR). FUR mixtures with VER, PIP and QRT were prepared by solvent evaporation, and mixtures with ARG were prepared by spray drying in 1:1 and 1:2 molar ratios. The solid-state properties of the mixtures were characterized with X-ray powder diffraction (XRPD), Fourier-transform infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC) in stability studies under different storage conditions. Simultaneous dissolution/permeation studies were conducted in side-by-side diffusion cells with a PAMPA (parallel artificial membrane permeability assay) membrane as a permeation barrier. It was observed with XRPD that ARG, VER and PIP formed co-amorphous mixtures with FUR at both molar ratios. DSC and FTIR revealed single glass transition values for the mixtures (except for FUR:VER 1:2), with the formation of intermolecular interactions between the components, especially salt formation between FUR and ARG. The co-amorphous mixtures were found to be stable for at least two months under an elevated temperature/humidity, except FUR:ARG 1:2, which was sensitive to humidity. The dissolution/permeation studies showed that only the co-amorphous FUR:ARG mixtures were able to enhance both the dissolution and permeation of FUR. Thus, it is concluded that formulating co-amorphous salts with ARG may be a promising option for poorly soluble/permeable FUR.